Analisis Prestasi dari Perspektif Manajemen: Studi pada PT.Estika Tata Tiara Tbk - Purba, Dea Natalia; Simanjuntak, Putri Christina (Jurnal Sistem Informasi, Akuntansi dan Manajemen, 2024)
This research aims to analyze the company's achievements from a management perspective; the object of the research is PT. Estika Tata Tiara Tbk. This data can be accessed and obtained from https://ir.kibif.com/reports/ for 2020—2022. The method we use uses a descriptive approach; this data is analyzed by focusing on ratios, which are often used to analyze management perspectives. The results of this research show that PT. Estika Tata Tiara Tbk is less than optimal because it can be seen from its financial ratios, which are less stable, and the net sales position ratio has experienced a significant decline, so PT. Estika Tata Tiara Tbk has the potential to experience bankruptcy.